Surface Alterations of Resin Composites: Press-on-Force-Guided Brushing Simulator with Calcium-Active Whitening- Toothpastes - SEVER, DENİZ MELTEM; DOĞU KAYA, BENGÜ; MANAV, AYBİKE; ALKAN, ELİF; YILMAZ ATALI, PINAR; KORKUT, BORA; TAĞTEKİN, DİLEK (My University, 2023)
Introduction: The purpose was to investigate the surface roughness and the color changes of nanohybrid and microhybrid resin composites subjected to calcium active whitening toothpastes with different RDA values through a novel Press-on Force-Guided (PFG) Brushing Simulator. Material and Methods: Twenty-eight disc-shape samples (10x2mm) of a nanohybrid (Herculite, Kerr) and a microhybrid (Z250, 3M) composites were prepared and randomly divided into 4 subgroups (n=7). The samples were polymerized with a LED-curing unit with an irradiance of 1000 mW/cm2 (Valo Cordless, Ultradent). Finishing and polishing procedures were performed with 2 fine grits of Sof-Lex Discs (3M). Samples were stored in distilled water at 37°C for 24 hours. Composite samples were brushed with a medium-bristle toothbrush (ROCS Pro 5940, ROCS) using the PFG brushing simulator (Marmara University, Turkey) for 60.000 strokes (correspondence to 6 years clinically) in a slurry containing toothpaste with 120 RDA (Ca Active Whitening, ROCS) and 70 RDA (Electro Whitening, ROCS) under 300-320g load (200 strokes/min). In particular, surface roughness (Ra) and color change (ΔE) were investigated utilizing profilometer (MarSurf PS 10, Mahr) and spectrophotometer (Easy-Shade-5, VITA). Analysis of variance was used for repeated measurements; Bonferroni test was used for pairwise comparisons. The level of significance was set at p<0.05. Results: After brushing Ra values did not show a significant difference (p>0.05) except Herculite group brushed with Electro whitening (p=0.05) which showed the most roughness change (36.99%). There is a significant difference between Herculite (1.163±0.701) and Z250 (0.400±0.154) in Ra values after electro-whitening brushing (p=0.002). No significant color change was observed in any group, regardless of composite or tooth-paste type (p>0.05). ΔE values of Herculite (1.007±0.463; 1.100±0.452) and Z250 (1.558±0.618; 1.196±0.835) brushed with Ca Active Whitening and Electro Whitening toothpastes were less than 1.8 respectively. Conclusion: Tooth brushing with Ca active whitening toothpastes (different RDA values) affected differently on the surface roughness of Herculite and Z250 due to their filler and resin composition, but there is no effect on color. Keywords: brushing simulator, resin composite, whitening toothpaste, surface roughness, color change
Keywords: brushing simulator; resin composite; whitening toothpaste; surface roughness; color change